TmToll-7 Plays a Crucial Role in Innate Immune Responses Against Gram-Negative Bacteria by Regulating 5 AMP Genes in Tenebrio molitor - Park, Soyi; Jo, Yong Hun; Park, Ki Beom; Ko, Hye Jin; Kim, Chang Eun; Bae, Young Min; Kim, Bobae; Jun, Sung Ah; Bang, In Seok; Lee, Yong Seok; Kim, Yu Jung; Han, Yeon Soo (Frontiers in Immunology, 2019)
Although it is known that the Drosophila Toll-7 receptor plays a critical role in antiviral autophagy, its function in other insects has not yet been reported. Here, we have identified a Toll-like receptor 7 gene, TmToll-7, in the coleopteran insect T. molitor and examined its potential role in antibacterial and antifungal immunity. We showed that TmToll-7 expression was significantly induced in larvae 6 h after infection with Escherichia coli and Staphylococcus aureus and 9 h after infection with Candida albicans. However, even though TmToll-7 was induced by all three pathogens, we found that TmToll-7 knockdown significantly reduced larval survival to E. coli, but not to S. aureus and C. albicans infections. To understand the reasons for this difference, we examined the effects of TmToll-7 knockdown on antimicrobial peptide (AMP) gene expression and found a significant reduction of E. coli-induced expression of AMP genes such as TmTenecin-1, TmDefensin-1, TmDefensin-2, TmColeoptericin-1, and TmAttacin-2. Furthermore, TmToll-7 knockdown larvae infected with E. coli showed significantly higher bacterial growth in the hemolymph compared to control larvae treated with Vermilion dsRNA. Taken together, our results suggest that TmToll-7 plays an important role in regulating the immune response of T. molitor to E. coli.